A new species of false spider crab of the genus Elamena H. Milne Edwards, 1837 (Crustacea: Decapoda: Brachyura: Hymenosomatidae), from Davao Gulf, Philippines - Husana, Daniel Edison M.; Kase, Tomoki; Mendoza, Jose Christopher E. (Zootaxa, 2013)
A new species of hymenosomatid crab of the genus Elamena H. Milne Edwards, 1837, is described from the island of Samal, in the Davao Gulf, Mindanao, southern Philippines. Elamena samalensis sp. nov. belongs to the Elamena truncata species-group and is most similar to E. simplidenta Ng & Chuang, 1996, in the general form of the carapace and in the presence of only one subdistal tooth on the ambulatory dactyli. It can be distinguished from this species, however, by its more projecting rostrum, relatively longer and more slender ambulatory legs, and by the pointed apex of the female ple-otelson.